L’historien, le code et l’ordonnance - Hélène Fernandez (Les Dossiers du GRIHL)
This article is a quick survey of chapter 14 of La Vie de Michel de Marillac by Nicolas Lefèvre de Lézeau, “De l’ordonnance de 1629”. The tone here is very defensive. The history of the huge legislative piece of work proposed by Lefèvre de Lézeau almost only quotes papers written by Marillac himself as a defense. The Ordonnance was indeed immediately ridiculed by libels, to the point that it is now generally known under the derisive nickname “Code Michau”. Therefore, it did not become the great public Code Marillac had hoped, but the failed work of a mocked private person. In the long term, however, the Code Michau became a sort of subterranean reference, admired by many but cited by few. This conclusion should help us re-examine the way we think about all legislative texts.